Ground-based Optical Transmission Spectroscopy of the Nearby Terrestrial Exoplanet LTT 1445Ab - Hannah Diamond-Lowe; João M. Mendonça; David Charbonneau; Lars A. Buchhave (The Astronomical Journal, 2023)
Nearby M-dwarf systems currently offer the most favorable opportunities for spectroscopic investigations of terrestrial exoplanet atmospheres. The LTT 1445 system is a hierarchical triple of M dwarfs with two known planets orbiting the primary star, LTT 1445A. We observe four transits of the terrestrial world LTT 1445Ab ( R = 1.3 R _⊕ , M = 2.9 M _⊕ ) at low resolution with Magellan II/LDSS3C. We use the combined flux of the LTT 1445BC pair as a comparison star, marking the first time that an M dwarf is used to remove telluric variability from time-series observations of another M dwarf. We find H α in emission from both LTT 1445B and C, as well as a flare in one of the data sets from LTT 1445C. These contaminated data are removed from the analysis. We construct a broadband transit light curve of LTT 1445Ab from 620 to 1020 nm. Binned to 3 minute time bins, we achieve an rms of 49 ppm for the combined broadband light curve. We construct a transmission spectrum with 20 spectrophotometric bins each spanning 20 nm and compare it to models of clear, 1× solar composition atmospheres. We rule out this atmospheric case with a surface pressure of 10 bars to 3.2 σ confidence, and with a surface pressure of 1 bar to 3.1 σ confidence. Upcoming secondary eclipse observations of LTT 1445Ab with the James Webb Space Telescope will further probe the cases of a high-mean-molecular-weight atmosphere, a hazy or cloudy atmosphere, or no atmosphere at all on this terrestrial world.